2014
DOI: 10.1021/nn500110a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Containing Nanoparticle-Stabilized Liposomes for Topical Antimicrobial Delivery

Abstract: Adsorbing small charged nanoparticles onto the outer surfaces of liposomes has become an effective strategy to stabilize liposomes against fusion prior to “seeing” target bacteria, yet allow them to fuse with the bacteria upon arrival at the infection sites. As a result, nanoparticle-stabilized liposomes have become an emerging drug delivery platform for treatment of various bacterial infections. To facilitate the translation of this platform for clinical tests and uses, herein we integrate nanoparticle-stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(153 citation statements)
references
References 48 publications
4
143
0
2
Order By: Relevance
“…In addition, the fluorescence signal was exclusively and evenly distributed around the bacterial nucleoids, and the image clearly reflected the characteristic spiral shape of H. pylori bacteria. Therefore, the microscopic observation, consistent with our previous studies (15), confirms the fusion of LipoLLA with H. pylori.…”
Section: Resultssupporting
confidence: 92%
“…In addition, the fluorescence signal was exclusively and evenly distributed around the bacterial nucleoids, and the image clearly reflected the characteristic spiral shape of H. pylori bacteria. Therefore, the microscopic observation, consistent with our previous studies (15), confirms the fusion of LipoLLA with H. pylori.…”
Section: Resultssupporting
confidence: 92%
“…Gao et al demonstrated that hydrogels containing Au NP‐stabilized liposomes displayed excellent antibacterial properties on S. aureus without skin toxicity to mice ( Figure 4 ). 45 In their research, the carboxyl‐modified Au NPs were absorbed onto the outer surfaces of cationic liposomes as stabilizers. The hydrogel formulation allowed for controllable viscoelasticity and tunable liposome release rate.…”
Section: Inorganic Antibacterial Agent‐incorporated Hydrogelsmentioning
confidence: 99%
“…Tissues from mice at 21 days post-injection were harvested and H&E-or TUNEL-stained, as described previously [56][57][58][59]. Cross-sections of epidermal layers of H&E-stained mouse previously exposed to HSA-SH/PEG-MAL hydrogel exhibited no significant inflammatory or toxicological responses as compared with non-exposed normal skin.…”
Section: Biocompatibility Of Hsa-sh/peg-mal Hydrogelmentioning
confidence: 99%